2017
DOI: 10.1016/j.tourman.2017.06.004
|View full text |Cite
|
Sign up to set email alerts
|

Risk-tourism, risk-taking and subjective well-being: A review and synthesis

Abstract: This paper seeks to conceptualize the potential relationship between subjective well-being and risk-taking within 'risk-tourism' i.e. specific activities that involve the potential for physical injury and death and require participants to develop competencies with which to overcome the risks associated with those activities. Literature is reviewed in three fields of inquiry: subjective wellbeing, with specific reference to the interactions between wellbeing and tourism behavior, risktaking in tourism and risk-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
46
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(55 citation statements)
references
References 53 publications
1
46
1
Order By: Relevance
“…(Holm et al, 2017) NM "This paper seeks to conceptualize the potential relationship between subjective well-being and risk-taking within 'risk-tourism' …" (p. 115). (Jenkins & Romanos, 2014) Bali "This comparative case study (…) focuses on the economic and artistic well-being of artists in three communities" (p. 293).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…(Holm et al, 2017) NM "This paper seeks to conceptualize the potential relationship between subjective well-being and risk-taking within 'risk-tourism' …" (p. 115). (Jenkins & Romanos, 2014) Bali "This comparative case study (…) focuses on the economic and artistic well-being of artists in three communities" (p. 293).…”
Section: Resultsmentioning
confidence: 99%
“…Human resources practices of support to these travelers were predictive of vigor and satisfaction in work travel. In risktourism, Holm et al (2017) noted that the literature suggests that people that are risk inclined may benefit from higher levels of subjective wellbeing when partaking in risk experiences. The researchers found that 'emotion' is a common attribute between risk-taking tourism and subjective wellbeing.…”
Section: Reference Location Paper Aim(s)mentioning
confidence: 99%
“…Lupton (2013) 61 explains that risk-taking in terms of sexual practices such as sadomasochism shares characteristics with activities such as extreme sports or adventure travel since both are associated with injury or disease and considered risky by the majority society. However, sports and travel can be encouraged and seen as self-improvement activities worth understanding and admiration 68 while practices such as barebacking (anal intercourse in which condom use is explicitly and intentionally excluded) 69 or bug chasing (desire to deliberately become HIV infected) 70 are viewed in a negative light 71 .…”
Section: Risk and Sexual Riskmentioning
confidence: 99%
“…As also seen in other studies, travelling to Berlin changed many interviewees in terms of gay identity and preferences as well as their perception of Sweden and Swedish gay culture when returning home and being "homecomers" 110,112 . This means both that they may implement new practices at home and that they may develop a new relation and attitude towards risk 68 .…”
Section: Comparison To Previous Studiesmentioning
confidence: 99%
See 1 more Smart Citation